The Differences between Thai and Indonesian Undergraduates in Pronouncing Plural Nouns and Third Singular Present Verbs due to Progressive Assimilation - Sofa Zakiyatul Muna (IAIN Salatiga, 2015)
Pronunciation is an important aspect in learning English and it is varied in different area. There are several types of dialect differences in speaking English and geographical dialect is one of them. In pronouncing plural verbs and third singular present verbs in English, the differences are happened. This research investigates the differences between Thai and Indonesian undergraduates in pronouncing plural nouns and third singular present verbs with s/es ending. The aim of this research are to find out the differences and similarities between Thai and Indonesian undergraduates in pronouncing plural nouns and third singular present verbs and the factors that influence it. The design of this research is case study by investigating Thai and Indonesian undergraduates of IAIN Salatiga in several period of time. Data is collected through documentation and interview. Documentation is conducted by recording respondents’ pronunciation. The recording is analyzed and combined with interview report to answer research problems. From the analysis, it is found that the differences and similarities of Thai and Indonesian undergraduates are substitution and omission of s/es suffix pronunciation. It is influenced by the geographic dialects and the existence of consonants in native language.